Social Communication Research through Visual Methods: An Internacional Methodological and Instrumental Review - Marin, Alba; Carrillo Durán, María Victoria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This paper presents a systematic methodological-instrumental review of research in social communication using visual methods. The main objective is to map the current state of re-search involving this specific methodological approach. The study explores the international use of visual methods in articles indexed in WoS and Scopus, the leading scientific databases. It examines visual creation as a mediated methodological lens for studying social communica-tion and offers a guide for future research in the field. To achieve this, the article provides a detailed description of the visual techniques applied, their practical uses, and the research objects analysed across 30 studies. The findings reveal a growing adoption of visual methods in communication studies, a trend reflected in high-impact journals